If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -8 = -20 Reorder the terms: -8 + 10x = -20 Solving -8 + 10x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 10x = -20 + 8 Combine like terms: -8 + 8 = 0 0 + 10x = -20 + 8 10x = -20 + 8 Combine like terms: -20 + 8 = -12 10x = -12 Divide each side by '10'. x = -1.2 Simplifying x = -1.2
| 13(v+3)-4v=3(3v+1)-7 | | 36x^2+246x-336=0 | | 16x-7=3(5x+5)-8 | | 6x^2-41x+56=0 | | 5X-1-3=1 | | -7(v+4)+4v+7=6v+11 | | -3(-4x-7)+(5-6x)=8 | | 7x-33=4 | | r^2-11rg+28g^2= | | -8=22t-6t^2 | | 8(x-6)-3x=5(x-9)-3 | | 2x^3-32x^2-450x= | | (x+2)+7x-8=0 | | -7(v+4)+3v+7=8v+7 | | 5r+r^2-24= | | 2x+2y+80=180 | | .33x+1.33=1-.25x+1.25 | | 2x+2-5(x+1)=5x+4 | | b^2-11b+28= | | x^3+2x^2-6x-12= | | 4x^3+5x^2-8x-10= | | 0=4+2x^2 | | -4[4-(3b+4)]=5-4(3b+9) | | 4m-2.50=14.30 | | (x+2)(x+2)+8x=0 | | 2x^8+2x^7-18x^6+10x^5= | | 0=20x-2x^2-4-2x^2 | | -4[4-(3b+4)]=7-4(3b+8) | | 5x^4y^6+10x^5y^5= | | (2ln(6x)x^2)-(x^2)= | | x-3+4x=-3+11x | | -0.09p-0.04(4-4p)=0.02(p-3)-0.1 |